Sustainable Nutrient-Rich Food Production during COVID-19 Pandemic through Year-Round Vegetable Farming Using Hydroponic Technique - S. M. Rezaul Karim; Raisa Osama (Chemistry Proceedings, 2022)
The impact of the ongoing COVID-19 pandemic has caused disastrous food shortages and increased food prices due to the disruption of agricultural systems and activities. Less consumption of nutrient-rich foods made the people more susceptible to COVID-19 infection during the pandemic. The situation resulted in a pivot to develop technology for economic and year-round production of nutrient-rich vegetables to alleviate malnutrition and to improve the immunity of the human body. Hydroponic farming (growing plants without soil) is a resilient food production system which provides perfect conditions for better and faster growth. This study involved the estimation of the total cost of establishing a polyhouse; setting up nutrient film technique (NFT) hydroponic system, the production costs of selected five vegetables, namely, tomato, broccoli, capsicum, lettuce and cabbage; the determination of their annual production and gross income based on prevailing market prices; and the net profits from hydroponic farming techniques. An amount of BDT 18.75 million (USD 0.22 million) could be earned by growing the selected five vegetables in a polyhouse of 100 m × 75 m size following the NFT technique of hydroponic farming. By investing BDT 31.56 million with a concurrent annual addition of BDT 0.59 million from the 2nd year, an amount of BDT 1.17 million net profit per year can be achieved. If the farmer pays a loan of BDT 0.60 million per year, a profit of BDT 0.56 million can still be earned every year and all the debts can be paid within eight years.